Uncovering the Key Drivers Behind Undergraduates’ Willingness to Embrace Mobile Learning in Sichuan, China - Wei, Zeng (Scholar: Human Sciences, 2026)
Purpose: The purpose of this research was to explore the effects of perceived ease of use, perceived usefulness, perceived enjoyment, facilitating conditions, social influence, and quality of service on undergraduates’ behavioral intention to use mobile learning in Sichuan, China. Research design, data, and methodology: The conceptual framework was built to combine the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT) theory. A quantitative method with the target population was adopted through distributing questionnaires. After the index of Item–Objective Congruence (IOC), pilot test, Confirmatory Factor Analysis (CFA), and Structural Equation Modeling (SEM), the data of 467 valid responses would be analyzed for testing the research hypotheses proposed. Results: The Research results show that the use of mobile learning in higher education and the perceived ease of use significantly influenced perceived usefulness, and both quality of service and perceived usefulness were the main driving factors for undergraduates’ behavioral intention. Additionally, perceived enjoyment and facilitating conditions had a certain influence. Conclusions: This study’s findings supported how higher education institutions urge students to use mobile learning in their life and learning processes. These findings have important implications for prompting the usage of mobile learning in the context of higher education.